Performance of an anaerobic baffled filter reactor (ABFR) - aerobic attached film bioreactor (AAFR) system in semi batch or continuous mode for treating organic wastewater dissertation - Allera, Andresa S.
Combination of anaerobic and aerobic wastewater treatment processes is employed for less energy requirement and simple aeration. In this study, the anaerobic reactor combines the characteristics of an attached film process in an anerobic baffled reactor while the subsequent aerobic treatment is carried out in a fixed film type reactor.